Stress and academic engagement among Saudi undergraduate nursing students: The mediating role of emotion regulation and emotional intelligence - Sarah Alkharj; Yasir S. Alsalamah; Rabia Allari; Maryam Saad Alharbi; Thamer Alslamah; Lisa Babkair; Safiah Labani; Mirna Fawaz (Wiley, 2024)
Abstract Aim To assess the mediating role of emotion regulation and emotional intelligence in the relationship between stress and academic engagement among Saudi undergraduate nursing students. Design This study employed a quantitative cross‐sectional research design. Methods The study recruited 367 Saudi undergraduate nursing students at a major Saudi university. Structural equation modelling was used to explore the mediational model. Results The results of the ANOVA and Welch F‐test demonstrated that the emotional intelligence, emotional regulation and academic engagement scores were statistically significantly different according to stress levels (p‐values <0.01). Perceived stress has a statistically significant moderate negative correlation with academic engagement and emotional intelligence and a strong negative correlation with emotional regulation. The results also showed that academic engagement had a statistically significant moderate positive association with emotional intelligence and emotional regulation. Results indicate that stress and academic engagement are negatively correlated among Saudi undergraduate nursing students. It focuses on the balancing functions of emotional regulation and emotional intelligence, highlighting their ability to lower stress levels and improve academic engagement. No Patient or Public Contribution.